Um estudo do diagrama de Voronoi para dois pontos geradores específicos com um obstáculo circular - Lima, Rafael Pereira de (2020)
In this work, we study concepts related to the Voronoi diagram, an important geometric data structure for solving proximity problems. Its construction takes place by comparing points arranged in a certain space and specific points, called the sites or generating points. Points that are the same distance from two neighboring sites make up the border of the diagram. There are algorithms that allow to build this diagram when polygonal obstacles are inserted between the sites. However, these algorithms are not useful when these obstacles have other formats. In this sense, we propose a computational algorithm to determine the boundary of the Voronoi diagram when there is a circular obstacle between two generating points arranged in the flat space R2.